Data Source Analysis of Computerized Management Accounting Based on Data Warehouse and Mobile Edge Computing. (8th March 2022) - Guo, Yanping
Abstract : Accounting work is more efficient when it is computerized, and the rate of errors is lower. The incentive mechanism should be improved before the development of management accounting practice in businesses. The emotion of employees in enterprises is a determinant of the spread of management accounting practice in businesses. Employees' resistance to management accounting practice can be effectively addressed through incentive mechanisms. As a result, in order to encourage the growth of management accounting in businesses, they must first create a perfect management accounting incentive mechanism. The implementation of a management accounting information system is made more difficult by these new categories. The construction of a management accounting information system based on BI and mobile edge computing is systematically discussed in this study. BI has the advantage of being able to model in a variety of ways, process large amounts of data efficiently, and provide managers with actionable data quickly. To realize the quantitative analysis of cost, income, and input-output, the system employs advanced technologies such as data warehouse modeling, data acquisition, data display, and security design. Management accounting has emerged as the best choice for the innovation of enterprise management mode as an accounting service for the internal management of businesses. Big data in management accounting serves as a company's "asset, " providing a wealth of information. It has become critical to understand how to mine and use big data information to provide a foundation for management accounting. This study explains how to collect data, prepare data, establish a model, mine data, and analyze data using a big data and mobile edge computing algorithm and identifies the key indicators affecting enterprise management accounting risk analysis through empirical analysis. The study of the diffusion mechanism and influencing factors of management accounting practice within enterprises and between enterprise clusters can help promote the development of management accounting practice and speed up the construction of China's localized management accounting system.